ALIH FUNGSI LAHAN PERTANIAN MENJADI KAWASAN PARIWISATA BERBASIS GOOD GOVERNANCE DALAM MEWUJUDKAN TERTIB TATA RUANG - Serang, Tasya Damaris Nahak (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
The purpose of the control is to realize an orderly land use, so that the function of space in an area is in accordance with the planning done by the government, especially local government. Batu city development which has been very rapid, it is known that the conversion of agricultural land in Batu City continues to increase. As mentioned above, Batu City Government has made various efforts to implement controls to maintain food security and maintaining agricultural land is relatively limited given the urgency of the general plan and detailed plans, that the consideration of the importance of regional spatial dimension is the key issue in regional development, especially in addressing the issue of land use conversion.